2016
DOI: 10.7287/peerj.preprints.2438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative genomics of Pseudomonas syringae pathovar tomato reveals novel chemotaxis pathways associated with motility and plant pathogenicity

Abstract: Comparative genomics of Pseudomonas syringae pathovar tomato reveals novel chemotaxis pathways associated with motility and plant pathogenicity. 15 Abstract 16 The majority of bacterial foliar plant pathogens must invade the apoplast of host plants through 17 points of ingress, such as stomata or wounds, to replicate to high population density and cause 18 disease. How pathogens navigate plant surfaces to locate invasion sites remains poorly 19 understood. Many bacteria use chemical-directed regulation of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…It is pertinent to note that, in Ralstonia solanacearum and Pseudomonas syringae pv. tomato , it has been shown that the mutants defective in the chemotaxis system exhibit reduced virulence when inoculated by the natural mode of infection (spray or dip inoculation), but are virulence proficient when inoculated directly by wound infection (Clarke et al ., ; Tans‐Kersten et al ., ; Yao and Allen, ). In contrast, it has been shown that Dickeya dadantii chemotaxis mutants exhibit defects in entry into plants, as well as reduced virulence, even after wound inoculation (Antunez‐Lamas et al ., ,).…”
Section: Discussionmentioning
confidence: 99%
“…It is pertinent to note that, in Ralstonia solanacearum and Pseudomonas syringae pv. tomato , it has been shown that the mutants defective in the chemotaxis system exhibit reduced virulence when inoculated by the natural mode of infection (spray or dip inoculation), but are virulence proficient when inoculated directly by wound infection (Clarke et al ., ; Tans‐Kersten et al ., ; Yao and Allen, ). In contrast, it has been shown that Dickeya dadantii chemotaxis mutants exhibit defects in entry into plants, as well as reduced virulence, even after wound inoculation (Antunez‐Lamas et al ., ,).…”
Section: Discussionmentioning
confidence: 99%
“…The genome analysis of PsPto indicates that it has four chemosensory pathways (Gumerov et al, 2019) and currently available data indicate that only one is involved in chemotaxis (Cerna‐Vargas et al, 2019; Clarke et al, 2016). In P. aeruginosa , the four chemosensory pathways appear to be insulated signalling routes (Matilla, Martin‐Mora, et al, 2021; Ortega, Fleetwood, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Stomata are the main entry points of PsPto into the plant apoplast, and previous studies have shown that PsPto is able to move towards open stomata (Melotto et al, 2006). It has also been observed that the mutation of cheA2 , encoding CheA of the chemotaxis pathway, causes a loss of chemotaxis and reduced fitness on plant hosts (Cerna‐Vargas et al, 2019; Clarke et al, 2016). This bacterium was found to perform chemotaxis towards amino acids, sugars, organic acids, and amides (Cerna‐Vargas et al, 2019; Cuppels, 1988; Kim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Gathering of Pto DC3000 around open stomata of Arabidopsis thaliana leaves suggested that Pto DC3000 can sense chemical signals released from the stomata [ 14 ]. Actually, the mutation of cheA2 in Pto DC3000 eliminated surface motility and reduced virulence on tomato and Arabidopsis [ 15 ]. We also found the requirements of cheA2 and cheY2 of Pta 6605 in chemotaxis and virulence on host tobacco plant (unpublished results).…”
mentioning
confidence: 99%